Corrosão acelerada por imersão modificada (ensaio CAIM) de estruturas de concreto armado contendo cinza da casaca de arroz e agua da mandioca brava - Trindade, Eduarda Carlesso (2013)
The corrosion in armatures is one of the most common pathologies found in structures of concrete, consisting in an electrochemical process, where the water in the concrete acts as an electrolyte. In this way, through the assays of accelerated corrosion (CAIM Tests), the resistance to corrosion in concrete of different mixtures was compared with the presence and absence of agricultural input so as rice husk and water from mandioca brava. The main objective of this work is to select mixture with similarity in resistance to compression and group content present the biggest resistance against the corrosion process amid containing chloride ions (solution simulating seawater – 35g/L NaCI), applying voltages of 15, 30 and 70V during 8, 24 and 48h. The cinder of rice husk and the water extracted from mandioca brava were characterized by the infrared spectroscopy analysis technics and by X-ray diffraction. The functional groups of silanol and carboxyl were detected in these agricultural byproducts and related to a proposed inhibition mechanism against the corrosion in armatures seen in CAIM data test. Electronic scanning microscopic analysis and dispersive X-ray energy collaborated to elucidated the proposed mechanism. While the studies in weight loss and chloride quantification in concrete after the CAIM test through the Mohr method helped in the validation of the assay results.